Pengaruh Lingkungan Kera, Motivasi Dan Budaya Organisasi Terhadap Komitmen Kerja (Pegawai Kantor Kecamatan Woha Kabupaten Bima) - Taslim, M.; Sunaryo, Hadi; Rizal, Mohammad (E-JRM : Elektronik Jurnal Riset Manajemen, 2024)
Abstract This research is a type of quantitative research. Where the population in this study was used as a sample using a saturated sample with a population of 75 respondents. By collecting data using the Correlation method, it aims to determine the partial influence between the variables of Work Environment, Motivation, and Organizational Culture on Employee Work Commitment. The Work Environment has a partial positive and significant influence on Work Commitment. Motivation does not have a partially significant effect on Work Commitment. Organizational Culture has a partially positive and significant influence on Work Commitment. The results of the Coefficient of Determination concluded that the magnitude of the influence of the variables Work Environment, Motivation, Organizational Culture on Work Commitment, with the rest influenced by other variables that were not studied in this study Keywords: Work Environment, Motivati on, and Organizational Culture towards Work Commitment